Bibliometric analysis of research on gut microbiota and bile acids: publication trends and research frontiers - Li, Xin; Lu, Can; Mao, Xue; Fan, Jiahong; Yao, Jianting; Jiang, Jingjie; Wu, Lele; Ren, Jingjing; Shen, Jun (Frontiers in Microbiology, 2024)
The gut microbiota is widely regarded as a "metabolic organ" that could generate myriad metabolites to regulate human metabolism. As the microbiota metabolites, bile acids (BAs) have recently been identified as the critical endocrine molecules that mediate the cross-talk between host and intestinal microbiota. This study provided a comprehensive insight into gut microbiota and BAs research through bibliometric analysis from 2003 to 2022. The publications on this subject had a dramatic upward trend. Although the USA and China have produced the most publications, the USA played a dominant role in this expanding field. Specifically, the University of Copenhagen was the most productive institution. Key research hotspots are the gutliver axis, short-chain fatty acid, cardiovascular disease, colorectal cancer, and farnesoid x receptor. The molecular mechanisms and potential applications of gut microbiota and BAs in cardiometabolic disorders and gastrointestinal cancers have the significant potential for further research.